Ética y responsabilidad empresarial en la sociedad globalizada (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The ethics is completely necessary in a global universe in which they prioritize the individual principles and interest front to the groups, because the economy, the policy and the daily life cannot work without a network of values like the confidence, the credibility, loyalty, honrades, the creativity, the efficiency, the coresponsibility.The companies that develop an ethical code contribute to that the economy fulfillshis authenticates mission when contributing to satisfy the human necessitieswith quality and justice by means of the rationalization with the productive activityand the lessening of its effects in the social and environmental surroundings.
Keywords: ethical behavior; ethical code; satisfacion of necessities.